The impact of bank-specific attributes on web-based disclosure practices of global banks / Manpreet Kaur and Mandeep Kaur - Kaur, Manpreet; Kaur, Mandeep (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2020)
This paper examines the extent of web disclosure practices of the top thirty global banks. The paper also investigates the impact of bank-specific characteristics such as bank size, financial performance and corporate governance on web disclosure practices. To analyse the extent of web disclosure practices, a disclosure index of 101 items of information was formulated. To check the hypotheses of the study, an OLS regression framework was estimated on a sample of the top thirty global banks. Descriptive analysis indicates that global banks’ web disclosure is at an acceptable level as the mean value was 73. The results show that large sized banks and banks that follow good corporate governance practices extensively use their websites to disclose information. On the contrary, financial performance negatively affects the extent of web-based disclosure in a global context. The study contributes to the existing literature of web based disclosure and the findings are useful for managers and investors. For managers it helps to meet the actual and potential informational needs of investors and for investors it helps in the decision to invest in a richer informational environment and better-assessed firm value.